Incentivizing Quantity and Quality of Care : Evidence from an Impact Evaluation of Performance-Based Financing in the Health Sector in Tajikistan - Ahmed, Tashrik; Arur, Aneesa; de Walque, Damien; Shapira, Gil (World Bank, Washington, DC, 2019)
This paper presents the results of an impact evaluation of a performance-based financing pilot in rural areas of two regions of Tajikistan. Primary care facilities were given financial incentives conditional on general quality and the quantity provided of selected services related to reproductive, maternal and child health, and hypertension-related services. The study relies on a difference-in-difference design and large-scale household and facility-based surveys conducted before the launch of the pilot in 2015 and after three years of implementation. The performance-based financing pilot had positive impacts on quality of care. Significant impacts are measured on facility infrastructure, infection prevention and control standards, availability of equipment and medical supplies, provider competency, provider satisfaction, and even some elements of the content of care, measured through direct observations of provider-patient interactions. While the communities in the performance-based financing districts reported higher satisfaction with the local primary care facilities, and despite the improvements in quality, the findings suggest moderate effects on utilization: among the incentivized utilization indicators, only timely postnatal care and blood pressure measurements for adults were significantly impacted.